Digital Health in Homecare: Exploring Nurses’ Needs for a Nursing Management Information System in Indonesia - Ni Made Diah Pusparini Pendet; Rai Sekar Widhi; Ni Putu Emy Darma Yanti (Bali Medical and Wellness Journal, 2025)
Background: The rising demand for homecare services in Indonesia highlights the urgent need for digital innovations to enhance nursing documentation and patient safety. Nursing Management Information Systems (NMIS) have the potential to strengthen continuity of care, efficiency, and sustainability. However, evidence from low-resource Southeast Asian settings remains limited. Methods: A cross-sectional survey was conducted among 106 homecare nurses in Bali, Indonesia. Data were collected using a structured questionnaire informed by the Technology Acceptance Model (TAM), focusing on system accessibility, completeness, security, and clinical decision support. Descriptive and bivariate analyses were performed. Results: A majority of respondents (84.9%) reported strong demand for NMIS. Key priorities included demographic information (63.2%), real-time patient health data (64.2%), and clinical decision-support features (64.2%). Nurses favored cloud/web-based platforms (23.6%) and documentation formats combining checklists with free-text entries (58.5%). Data security through username/password authentication was considered essential by 96.2% of participants. Associations were observed between years of experience and preferences for decision-support functions. Reported challenges included limited internet infrastructure and the need for digital literacy training. Conclusion: Homecare nurses in Indonesia demonstrate high demand for user-centered digital health solutions, particularly cloud/web-based NMIS with integrated decision-support tools. These findings provide a foundation for scalable and sustainable innovations in nursing informatics within low-resource contexts. Insights from Indonesia reflect shared challenges across ASEAN countries, aligning with initiatives in Thailand and the Philippines. Policy recommendations include investment in digital training, piloting NMIS in government-supported homecare, and strengthening regional interoperability frameworks.